Towards stem cell regeneration of the nucleus pulposus of the invertebral disc - Naqvi, Syeda Masooma (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2016)
Low back pain resulting from intervertebral disc (IVD) degeneration is a significant epidemiological problem and economic burden worldwide. IVD degeneration initiates within the nucleus pulposus (NP), a highly hydrated gel-like matrix rich in proteoglycans (PGs). NP cells can be as much as 8mm from the nearest blood vessel resulting in a tissue that is both nutrient and oxygen poor concomitant with a relatively low pH. With progressive degeneration, the nutrient supply to the disc is further reduced. Commercially available cell-based therapies such as autologous disc cell transplantation (ADCT) targeted to regenerate the NP region have demonstrated limited success with few instances of long term repair due to several shortcomings. First, the supply-demand, limited expansion capability and poor tissue forming capacity of NP cells derived from degenerated tissue are all pertinent limitations. Second, there is a risk of cell leakage. The overall objective ofthe thesis was to identify the specific conditions that can aid in regeneration ofthe nucleus pulposus, using bone marrow derived mesenchymal stem cells [BMSCs). To this end, this thesis set out to explore: i] the potential of BMSCs as an alternative cell source due to their availability in abundance, propensity to proliferate and ability to form NP-like tissue, ii] the development of a carrier biomaterial system to permit targeted delivery and to provide protection from the immune system.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; PhD Trinity College Dublin, 2016